Maternal and neonatal safety of COVID‐19 vaccination during the peri‐pregnancy period: A prospective study. Issue 1 (12th December 2022) - Li, Minghui; Hao, Jianzhen; Jiang, Tingting; Deng, Wen; Lu, Huihui; Wang, Shiyu; Wan, Gang; Xie, Yao; Yi, Wei
Abstract: Background: To investigate the safety of inactivated COVID‐19 vaccine in Chinese pregnant women and their fetuses when inoculated during the peri‐pregnancy period. Methods: Eligible pregnant women were prospectively collected and divided into a vaccine group ( n  = 93) and control group ( n  = 160) according to whether they had been vaccinated against COVID‐19 within 3 months before their last menstruation period (LMP) and after pregnancy. Demographic data of couples, complications during pregnancy and delivery of pregnant women, and data of newborns at birth were collected. Results: Sixty‐six women were vaccinated with a median time of 35.5 (range = 0–91) days before LMP, and 27 women were vaccinated with a median time of 17 (range = 1–72) days after LMP. The incidence of premature rupture of membrane (PROM) in the vaccine group was significantly higher than that in the control group (16.13% vs. 6.88%, p  = 0.019). Multivariate logistic regression analysis revealed that maternal peri‐pregnancy COVID‐19 vaccination was not an independent risk factor for PROM (odds ratio: 2.407, 95% confidence interval: 0.932–6.216, p  = 0.069). There was no difference in the incidence of other complications during pregnancy and delivery between the two groups. A total of 253 neonates were delivered, including two cases with congenital abnormalities in each group. The incidence of congenital abnormalities between the two groups was similar (2.15% vs. 1.25%, p  = 0.626). There was no difference in neonatal length, weight, head circumference, and Apgar score between the two groups ( p  > 0.05), but the incidence of neonatal jaundice in the vaccine group was significantly higher than that in the control group (20.43% vs. 7.5%, p  = 0.002). Multivariate logistic regression analysis revealed that maternal peri‐pregnancy vaccination, postpartum blood loss, cesarean section, 1‐min Apgar score, and paternal smoking were independent risk factors for neonatal jaundice. Conclusions: It is safe for pregnant women and their fetuses to be inoculated the inactivated COVID‐19 vaccine during the peri‐pregnancy period, but attention should be paid to neonatal jaundice.